Aiming the magic bullet: targeted delivery of imaging and therapeutic agents to solid tumors by pHLIP peptides - Yana K. Reshetnyak; Oleg A. Andreev; Donald M. Engelman (Frontiers Media S.A., 2024)
The family of pH (Low) Insertion Peptides (pHLIP) comprises a tumor-agnostic technology that uses the low pH (or high acidity) at the surfaces of cells within the tumor microenvironment (TME) as a targeted biomarker. pHLIPs can be used for extracellular and intracellular delivery of a variety of imaging and therapeutic payloads. Unlike therapeutic delivery targeted to specific receptors on the surfaces of particular cells, pHLIP targets cancer, stromal and some immune cells all at once. Since the TME exhibits complex cellular crosstalk interactions, simultaneous targeting and delivery to different cell types leads to a significant synergistic effect for many agents. pHLIPs can also be positioned on the surfaces of various nanoparticles (NPs) for the targeted intracellular delivery of encapsulated payloads. The pHLIP technology is currently advancing in pre-clinical and clinical applications for tumor imaging and treatment.